A novel method for assessing C-S-H chloride adsorption in cement pastes. (20th November 2019) - Chang, Honglei; Feng, Pan; Lyu, Kai; Liu, Jian
Highlights: The bound chloride content in cement pastes are evaluated at different carbonation time. The content of compounds associated with bound chlorides are quantitatively characterized. A feasible method for assessing C-S-H adsorbed chloride in cement pastes is proposed. The content of bound chloride adsorbed on C-S-H and combined in Friedel's salt is discussed. Abstract: The binding of chloride can retard the penetration process and is of important significance for the durability of concrete structures. The previous researches calculated the content of C-S-H absorbed chloride mainly through chemical synthesized C-S-H and thermodynamic modeling, rather than in real cement pastes. This study proposed a feasible method for assessing C-S-H adsorbed chloride in real cement pastes by utilizing the order of decomposition of Friedel's salt, Kuzel's salt and C-S-H gel during carbonation and the significant content difference between them. All the parameters used for analysis were obtained experimentally, and thus have high reliability. The content of bound chloride adsorbed on C-S-H and combined in Friedel's salt was determined with this novel method in pastes under two different exposure conditions. The results show that the adsorption amount of chloride within W50-N and W50-C on C-S-H of per unit mass is 0.00418 g and 0.00588 g separately, and the ratio of C-S-H adsorbed chloride to the total bound chloride in pastes is 49.1% and 46.0% respectively.